DIAGNOSIS AND MANAGEMENT OF HEMORRHOIDS : A SYSTEMATIC REVIEW - Gajah, Supriyadi; Martupa Lumbantoruan, Johannes (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Hemorrhoids are vascular tissues that naturally develop in the submucosa of the anal canal. They are composed of blood vessels with many arteriovenous connections, smooth muscle, and loose connective tissue, which explains why hemorrhoidal bleeding is usually brilliant red.Aims : This systematic review is to review the diagnosis and managements of hemorrhoids.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 7536 articles, whereas the results of our search on SAGEPUB brought up 4560 articles, our search on SCIENCE DIRECT brought up 5110 articles. The results of the search conducted for the last year of 2014 yielded a total 3250 articles for PubMed, 1369 articles for SAGEPUB and 1565 articles for SCIENCE DIRECT. In the end, we compiled a total of 8 papers, 5 of which came from PubMed, 1 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included eight research that met the criteria.Conclusion: In summary, the illness hemorrhoids is prevalent yet complicated. Patients who have hemorrhoidal signs and symptoms should be closely examined to rule out other possible masquerade conditions. Hemorrhoids can be managed in a variety of ways, and the best course of action depends on the unique needs of each patient as well as clinical considerations.